QCD flux tubes and anomaly inflow - Xiong, Chi. (2014)
We apply the Callan-Harvey anomaly-inflow mechanism to the study of QCD (chromoelectric) flux tubes, quark (pair) creation, and the chiral magnetic effect, using new variables from the Cho-Faddeev-Niemi decomposition of the gauge potential. A phenomenological description of chromoelectric flux tubes is obtained by studying a gauged Nambu–Jona-Lasinio effective Lagrangian, derived from the original QCD Lagrangian. At the quantum level, quark condensates in the QCD vacuum may form a vortexlike structure in a chromoelectric flux tube. Quark zero modes trapped in the vortex are chiral and lead to a two-dimensional gauge anomaly. To cancel it, an effective Chern-Simons coupling is needed and, hence, a topological charge density term naturally appears.